Indonesian Dance Education in Taiwan: Methods and Experiences as a Teacher - Anastasia Melati (Institut Seni Indonesia Yogyakarta, 2022)
Traditional dances are a type of performing arts passed down from previous generations. Some of these dances become the cultural heritage of a nation, and therefore, they require strategies and projects to preserve their traditional forms while promoting its contemporary articulations. This study examines the process of teaching Indonesian traditional dance to Taiwanese students and analyzes how this intangible cultural heritage is perceived by the students, not only as knowledge but also as cultural connectivity that links to the cultural and socio-political positioning of Taiwan. The study aims at investigating (a) the methods and results of dance pedagogy of Indonesian traditional dances under new socio-cultural contexts in Taiwan, (b) the cross-cultural issues of education in dance, i.e., transnational aesthetic values and ethnological concerns experienced in directing dance training. It intends to reveal how to teach the dances both as knowledge and as cultural connectivity between the two nations, the pedagogical challenges in the process, and the best methodology to teach foreign dances. The study hypothesizes that dance teaching requires the mastery of the techniques, theories, and cultural knowledge, and those who study dances need to learn about the cultural background and values of the dances. In practice, sessions on theoretical knowledge and cultural values take up different portions of classroom instructions depending on the backgrounds of the students. Observations are conducted through teaching academically to students at National Taiwan University and practically to Taiwanese professional artists and dancers. Teaching these two groups poses different challenges and requires two different methods. Pendidikan Tari Indonesia di Taiwan: Metode dan Pengalaman sebagai Guru. Tarian tradisional merupakan salah satu jenis seni pertunjukan yang diturunkan dari generasi sebelumnya. Beberapa dari tarian ini menjadi warisan budaya suatu bangsa, dan oleh karena itu, mereka membutuhkan strategi dan proyek untuk melestarikan bentuk tradisionalnya sambil mempromosikan artikulasi kontemporernya. Studi ini mengkaji pengajaran tari tradisional Indonesia kepada siswa Taiwan dan menganalisa bagaimana warisan budaya takbenda ini dirasakan oleh siswa, tidak hanya sebagai pengetahuan tetapi juga sebagai konektivitas budaya yang terkait dengan posisi budaya dan sosial-politik Taiwan. Tujuan penelitian ini adalah untuk menelaah (a) metode dan hasil pedagogi tari tradisional Indonesia dalam konteks sosial budaya baru di Taiwan, (b) isu lintas budaya pendidikan dalam tarian, yaitu nilai-nilai estetika transnasional dan masalah etnologis yang dialami dalam menjalankan pelatihan tari. Penelitian diharapkan dapat menjawab pertanyaan tentang bagaimana mengajarkan tarian bukan saja sebagai pengetahuan melainkan juga sebagai konektivitas budaya antara kedua negara, tantangan dalam proses mengajar, dan metodologi terbaik untuk mengajarkan tarian asing. Hipotesa penelitian ini adalah pengajaran tari membutuhkan penguasaan teknik, teori, dan pengetahuan budaya, dan mereka yang belajar tari perlu belajar tentang latar belakang budaya dan nilai-nilai tarian. Dalam praktiknya, sesi tentang pengetahuan teoretis dan nilai-nilai budaya mengambil porsi yang berbeda dari instruksi kelas tergantung pada latar belakang siswa. Observasi dilakukan melalui pengajaran akademis kepada mahasiswa di National Taiwan University dan secara praktis kepada seniman dan penari profesional Taiwan. Mengajar kedua kelompok ini mempunyai tantangan yang berbeda dan membutuhkan dua metode yang berbeda.